Recent Advances in Spinel Ferrite-Based Thin Films: Synthesis, Performances, Applications, and Beyond - Hao, Aize; Ning, Xueer (Frontiers in Materials, 2021)
This review provides a comprehensive overview of the recent advances in the various typical spinel ferrite-based thin films with controlled synthesis, their performances, applications in multifunctional material fields, fundamental scientific challenges, and beyond. Firstly, the crystal structures of spinel ferrite-based thin films are introduced. Secondly, recent progress in traditional synthesizing and novel methods for preparation of spinel ferrite-based films are highlighted. Thirdly, their magnetism, electricity, optics performances, and applications in advanced information technology, energy storage and conversion, and environmental conservation fields are also summarized and discussed in-depth. Some effective strategies for optimizing performances and further applications are summarized. Finally, the present review work ends with a short discussion concerning the challenges, opportunities, and future prospects of spinel ferrite-based thin films.